2009
DOI: 10.1002/hbm.20815
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow changes induced by pedunculopontine nucleus stimulation in patients with advanced Parkinson's disease: A [15O] H2O PET study

Abstract: Patients with advanced Parkinson's disease (PD) develop disabling axial symptoms, including gait disturbances, freezing and postural instability poorly responsive to levodopa replacement therapy. The pedunculopontine nucleus (PPN) is involved in locomotion, control of posture, and behavioral states [i.e. wakefulness, rapid eye movement sleep]. Recent reports suggested that PPN modulation with deep brain stimulation (DBS) may be beneficial in the treatment of axial symptoms. However, the mechanisms underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 43 publications
2
72
1
Order By: Relevance
“…We recognize that the inferential power of the present single-case study is limited, however, the improved response profile demonstrated by the participant, perhaps most notably at 5months follow-up, alludes to a practical patient benefit that, in our opinion, justifies larger-scale investigation. Although the biological basis of recovery was not investigated here, we speculate that the nonmotor gains point to activation of non-dopaminergic pathways and may underline the growing therapeutic relevance of the pedunculopontine nucleus given that it both sends and receives dense projections from areas with known vestibular responses and, when directly activated via deep brain stimulation, has been associated with heightened cognition and arousal (Ballanger et al, 2009). …”
Section: Discussionmentioning
confidence: 97%
“…We recognize that the inferential power of the present single-case study is limited, however, the improved response profile demonstrated by the participant, perhaps most notably at 5months follow-up, alludes to a practical patient benefit that, in our opinion, justifies larger-scale investigation. Although the biological basis of recovery was not investigated here, we speculate that the nonmotor gains point to activation of non-dopaminergic pathways and may underline the growing therapeutic relevance of the pedunculopontine nucleus given that it both sends and receives dense projections from areas with known vestibular responses and, when directly activated via deep brain stimulation, has been associated with heightened cognition and arousal (Ballanger et al, 2009). …”
Section: Discussionmentioning
confidence: 97%
“…4,5 The PPN modulates limb movements and locomotion. PPN neue-Pub ahead of print on August 11, 2010, at www.neurology.org.…”
Section: Discussionmentioning
confidence: 99%
“…5,26,27 The premovement beta excitatory drive from the SMA to the PPNR may be involved with formulation of motor program for movement executions. Thus, the beta rhythm in the human PPNR may be prokinetic rather than antikinetic.…”
Section: Event-related Desynchronization and Synchronizationmentioning
confidence: 99%
“…rCBF increases in prefrontal areas have been noted during unilateral PPN stimulation. 16 The discordance between the patterns of rCBF changes following PPN stimulation may reflect the few patients in both studies giving reduced power to detect subtle changes. Alternatively, the lack of prefrontal activation in our patients may represent degeneration in the ascending cholinergic projections from the PPN to the frontal cortex, which has been described in advanced PD, especially in patients with axial symptoms.…”
Section: Petmentioning
confidence: 99%